2002
DOI: 10.1007/s00415-002-0800-7
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation for multiple sclerosis

Abstract: Autologous HSCT suggest positive early results in the management of progressive MS and is feasible. These multicentre data suggest an association with significant mortality risks especially in some patient groups and are being utilised in the planning of future trials to reduce transplant related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
156
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(167 citation statements)
references
References 44 publications
2
156
0
9
Order By: Relevance
“…The authors found that patients with relapsing-remitting and secondary progressive MS subtypes, which have more inflammatory characteristics, had a progression-free survival rate of 78±13%, and among those with primary progressive MS, which is more degenerative, this rate was 66±23% during 3 years. 25 In 2006, the same group published an updated analysis of 143 cases with a 41.7-month follow-up: the disease remained stable or improved in 63% of patients and progressed in 37%. 26 Regimens that ablate the entire BM hematopoietic compartment are by definition myeloablative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that patients with relapsing-remitting and secondary progressive MS subtypes, which have more inflammatory characteristics, had a progression-free survival rate of 78±13%, and among those with primary progressive MS, which is more degenerative, this rate was 66±23% during 3 years. 25 In 2006, the same group published an updated analysis of 143 cases with a 41.7-month follow-up: the disease remained stable or improved in 63% of patients and progressed in 37%. 26 Regimens that ablate the entire BM hematopoietic compartment are by definition myeloablative.…”
Section: Introductionmentioning
confidence: 99%
“…34 The mortality rate of HSCT for MS in studies with relatively large samples is described in Table 1. [25][26][27][28][29][30][35][36][37][38][39][40][41][42][43][44][45] Although these studies use myeloablative conditioning regimens of varying intensity, non-myeloablative regimens have been advocated for autologous HSCT of autoimmune diseases. 46 Recently, one of these latter studies was published using CY/rATG and it reported no deaths among 21 patients with relapsing-remitting MS. 31 There is a controversy regarding the analysis of the immune system modifications as increases in naive CD4 þ T cells over memory cells 20 and the fact that more intensive regimens seem to present better results than less intensive regimens.…”
Section: Introductionmentioning
confidence: 99%
“…This early experience showed that although AHCT seemed to reduce gadolinium enhancement in brain MRI imaging it did not prevent progression of the disease or improve patients' outcome [11,12]. With increasing experience, patients with RRMS were increasingly treated and noted to have a more favorable response, with reduction in clinical relapses, MRI disease activity, and disability progression.…”
Section: History Of Ahct In Msmentioning
confidence: 99%
“…Initially, several regimens included the use of total body irradiation (TBI) [10] and busulfan [11,14,15]. These regimens were associated with high morbidity and mortality [14,16].…”
Section: History Of Ahct In Msmentioning
confidence: 99%
“…No approved treatments currently offer curative options for patients with MS. 13 While mortality risks of HSCT for the treatment of MS cannot be understated, 14,15 clinical results of Phase I/II trials [15][16][17][18] seem overall encouraging, particularly when objective MRI measures have been employed to monitor the evolution of inflammatory disease activity. 19,20 These results have prompted the design of controlled trials of HSCT vs standard therapy (mitoxantrone), which are planned to start in Europe and in the US in the near future.…”
Section: Exploring the Immunological Mechanisms Of Hsct In Msmentioning
confidence: 99%